Investıgatıon for Envıronmental Effects and Evaluatıon of Fıne Taılıngs from Tuncbılek Coal Processıng Plant/Turkey: Investıgatıon for Envıronmental Effects and Evaluatıon of Fıne Taılıngs from Tuncbılek Coal Processıng Plant/Turkey - Uçar, Ali; Şensöğüt, Cem; Ediz, Göktay (International Journal of Economic and Environmental Geology, 2018)
In energy production, coal still keeps its importance despite many environmental problems. Although Turkey is fortunate in terms of coal reserves, it is not possible to say the same for their quality. Unfortunately, most of the coal reserves in Turkey are of low quality. Therefore, they have high ash, moisture and sulphur contents. Increasing environmental concerns and the demands of new generation technologies make it necessary to clean the coal. Coals can be enriched at every stage as large, fine and slime, and are referred to by the same names in the tailings. Coarse and fine tailings can be stored dry, while coal in very fine size (-0.1 mm) is fed to the dams after not being enriched and dewatered at certain rates in Turkey. These residues are produced at Tunçbilek coal processing plant of Western Lignite Corporation (WLC), which is one of the oldest and most important coal preparation plants in Turkey, and during which the gravity processes are applied. The most important environmental problem here is that the ultra-fine slime, which is not enriched with high calorific values (kcal/kg), is charged to previously mined open pit holes. In addition, there are two ponds and an open pit hole in the vicinity of the plant where these remains were stocked in previous years. Tailing charging is still going on for another open pit hole at the plant. In this case, both the economic losses and the environmental problems are continuing as the coal is not recovered from these tailings. For this reason, it is necessary to completely dehydrate and store or enrich these tailings.